A pesquisa na formação docente no curso de pedagogia no CESP/UEA: um processo em construção - Souza, Eliseu da Silva (2015)
The research in the course of Pedagogy/CESP UEA needs to be taken by the group as an object of study to teacher training project. In addition, it must be part of educational material for activities in the classroom. Therefore, it is important to create groups of study to qualify the process, considering the Curricular Project of the course which establishes the research as the axis of teaching. This assertion is the result of a research on the teacher education in the Faculty of Education at the Centro de Estudos Superiores de Parintins/UEA, which has analyzed the research developed by students as a requirement for graduation. Therefore, we sought to answer the question of how to place the research as a subject in the Faculty of Education, that is, how the Course Completion works are performed. The theoretical support for the realization of this research was based on André (2013), Pacheco (2005), Demo (1996, 2003, 2010, 2011), Meksenas (2002), Moreira and Thaddeus (2011) Ghedin and Franco (2011), among others. The methodological procedures were based on a qualitative approach, which allows the use of different research strategies and methods for data collection. The subjects of the study were both the graduating students in 2012, from CESP/UEA (the ones who, in 2014, were already working in the classroom in kindergarten and elementary school in Parintins/AM) and the trainers teachers who worked in the guidance process for those researches. The collection and analysis of data were organized into three categories: 1) the construction of the research process; 2) the concern of adding research in the formation of the teacher in the school routine; and 3) the contribution (or not) of the research as a discipline in the teacher training process. To reach such goal, semi-structured interviews were conducted, and observations have been made in class, during the teaching practice in schools, both in urban and rural areas, where graduates were working. For the methodological development, the theoretical support was based on André (2013), Creswell (2007), Triviños (2008), Marconi and Lakatos (2011), Ghedin and Franco (2011). It is observed, therefore, that the research sets an important axis in the course of pedagogy at the Amazonas State University, but such value has not been assigned in teacher education yet.